A systematic review and meta-analysis on sub-microscopic Plasmodium infections in India: Different perspectives and global challenges - Nimita Deora; C.P. Yadav; Veena Pande; Abhinav Sinha (Elsevier, 2022)
Summary: Background: The long-term maintenance of parasite biomass below the detection threshold of microscopy may stymie malaria elimination. Variation in microscopists' competencies to detect and correctly identify parasite species reflect in microscopy sensitivity, resulting in incorrect species-specific burden. Methods: The study estimated Plasmodium SMI pooled burden from published reports using a random effect model & identifies their hotspots in India. The study applied a prediction model for the first time on Indian data, emphasizing the importance of such models that can predict PCR-prevalence from slide- prevalence. Findings: A total of 17,449 samples from 39 districts were examined for Plasmodium by microscopy and PCR. The overall heterogeneity in clinic-based and community-based studies was 91% and 96%, respectively, with the pooled prevalence of 3.63%. The SMI prevalence in individual studies ranged from 38.4% to 0.4%. Sensitivity of microscopy for mono-P. vivax (91%) was found to be better than mono-P. falciparum (82 %). But surprisingly, it was much lower for mixed PfPv (45%). Interpretation: Primary regional data in the form of SMIs hot spots should be generated from countries on the verge of malaria elimination, and genetic monitoring should be integrated into national programs, particularly in key areas for successful malaria elimination. Funding: Not applicable.